Music and Society: The Politics of Composition, Performance and Reception - Leppert, Richard D.; McClary, Susan (Cambridge Cambridge University Press, 1989)
Socially and politically grounded enterprises such as feminism, semiotics and deconstruction have effected a major transformation in the ways in which the arts and humanities are studied. This provocative volume of essays challenges the ideology that insists music occupies an autonomous sphere. By examining the ways in which music and society interact with and mediate one another within and across socio-cultural boundaries, these authors--musicologists, sociologists, cultural theorists--provide a sound argument.Show More Show Less
Keywords: Composing; Performance; Reception